Representasi Makna Perempuan Kuat pada Film Bolehkah Sekali Saja Kumenangis - Intania Berliany Utami; Nyoman Suardhita; Namira Fitria (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study analyzes the representation of the meaning of strong women in the main character, Tari, in the film Bolehkah Sekali Saja Ku Menangis using Roland Barthes' semiotic theory. The film emotionally depicts Tari’s life journey, from psychological pressure and harsh treatment within the family to the long process of rediscovering her true identity. Despite emotional wounds, Tari shows resilience and strength to rise. This study aims to identify how the meaning of a strong woman is constructed through cinematic elements such as visuals, dialogues, body expressions, and symbols in the film. Using a qualitative approach with Barthes' semiotic theory, the analysis focuses on the relationship between signs, denotative meaning, and connotative meaning in key scenes. Data was collected through in-depth observation and sign analysis of scenes that portray Tari's struggle, perseverance, and emotional transformation. The findings show that Tari represents a strong woman not only through physical endurance but also emotional resilience, self-empowerment, mental health awareness, and the courage to seek support. The film delivers a message about the importance of mental strength and women's courage in fighting for their rights and freedom. This study is expected to enrich the study of the representation of strong women in the media.